Are Chemical Journals Too Expensive and Inaccessible?: A Workshop Summary to the Chemical Sciences Roundtable - National Research Council (The National Academies Press, 2005)
On October 25-26, 2005, the Chemical Sciences Roundtable held a workshop to explore issues involving those who use and contribute to chemical literature, as well as those who publish and disseminate chemical journals. As a follow-up to the workshop, a summary was written to capture the presentations and discussions that occurred during the workshop. As a forum to discuss chemistry journals within the larger context of scientific, technical and medical journal publishing, the workshop covered whether chemists and chemical engineers have unique journal needs and, if so, whether these needs are being met in the current journal publishing environment. Workshop participants also tackled how open access publishing might be applied to the chemical literature, such as to provide authors more freedom to distribute their articles after publication and allowing free access to chemical literature archives.
Keywords: Math, Chemistry, and Physics; Education

Opportunities in High Magnetic Field Science - National Research Council (The National Academies Press, 2005)
High-field magnets—those that operate at the limits of the mechanical and/or electromagnetic properties of their structural materials—are used as research tools in a variety of scientific disciplines. The study of high magnetic fields themselves is also important in many areas such as astrophysics. Because of their importance in scientific research and the possibility of new breakthroughs, the National Science Foundation asked the National Research Council to assess the current state of and future prospects for high-field science and technology in the United States. This report presents the results of that assessment. It focuses on scientific and technological challenges and opportunities, and not on specific program activities. The report provides findings and recommendations about important research directions, the relative strength of U.S. efforts compared to other countries, and ways in which the program can operate more effectively.
Keywords: Math, Chemistry, and Physics; Policy for Science and Technology

Catalyzing Inquiry at the Interface of Computing and Biology - National Research Council (The National Academies Press, 2005)
The remarkable growth of both computer science and biology in recent decades has drawn attention to their areas of intersection. Both fields have much in common; they are among the most rapidly changing fields of science, they both deal with very complex systems, and they both have profound implications for science and society. To examine the potential for greater interaction between the two fields, the National Research Council undertook a study looking at ways computational science can aid the development and understanding of biology and how the biological sciences might facilitate new and more powerful computational methods. This book presents an analysis of the potential synergies at the interface of the two fields and of ways to develop new collaborations between researchers in both areas to exploit those synergies. The book provides a large sample of well-documented examples of these interactions. The study concludes that the impact of computing on biology will be deep and profound and span virtually all areas of life science research. Computational biology will ultimately become part of the biological sciences. The impact of biology on computing is less certain, but could be substantial and should be pursued.
Keywords: Biology and Life Sciences; Computers and Information Technology; Math, Chemistry, and Physics; Surveys and Statistics

Mathematics and 21st Century Biology - National Research Council (The National Academies Press, 2005)
The exponentially increasing amounts of biological data along with comparable advances in computing power are making possible the construction of quantitative, predictive biological systems models. This development could revolutionize those biology-based fields of science. To assist this transformation, the U.S. Department of Energy asked the National Research Council to recommend mathematical research activities to enable more effective use of the large amounts of existing genomic information and the structural and functional genomic information being created. The resulting study is a broad, scientifically based view of the opportunities lying at the mathematical science and biology interface. The book provides a review of past successes, an examination of opportunities at the various levels of biological systems— from molecules to ecosystems—an analysis of cross-cutting themes, and a set of recommendations to advance the mathematics-biology connection that are applicable to all agencies funding research in this area.
Keywords: Biology and Life Sciences; Math, Chemistry, and Physics; Surveys and Statistics